Isolation of sophorose during sophorolipid production and studies of its stability in aqueous alkali: epimerisation of sophorose to 2-O-β-d-glucopyranosyl-d-mannose. (8th February 2016) - AL-Jasim, Ammar; Davis, Mark; Cossar, Douglas; Miller, Timothy; Humphreys, Paul; Laws, Andrew P.
Highlights: Isolation of sophorose from sophorolipid production waste streams. Evidence for enzymes within fermentation liquors able to catabolise sophorolipids. C2-Epimerisation of sophorose and isolation of 2-O-β-D -glucopyranosyl-α/β-D -mannose. At moderately basic pHs (12.5) β-(1, 2)-linked disaccharides do not undergo peeling. At moderately basic pHs (12.5) β-(1, 2)-linked disaccharides do not undergo hydrolysis. Graphical abstract: Isolation of β-(1, 2)-linked disaccharides from sophorolipid production Abstract: NMR and anion exchange chromatography analysis of the waste streams generated during the commercial production of sophorolipids by the yeast Candida bombicola identified the presence of small but significant quantities (1% w/v) of free sophorose. Sophorose, a valuable disaccharide, was isolated from the aqueous wastes using a simple extraction procedure and was purified by chromatography on a carbon celite column providing easy access to large quantities of the disaccharide. Experiments were undertaken to identify the origin of sophorose and it is likely that acetylated sophorose derivatives were produced by an enzyme catalysed hydrolysis of the glucosyl-lipid bond of sophorolipids; the acetylated sophorose derivatives then undergo hydrolysis to release the parent disaccharide. Treatment of sophorose with aqueous alkali at elevated temperatures (0.1M NaOH at 50 °C) resulted in C2-epimerisation of the terminal reducing sugar and its conversion to the corresponding 2-O-β-d -glucopyranosyl-d -mannose which was isolated and characterised. In aqueous alkaline solution β-(1, 2)-linked glycosidic bonds do not undergo either hydrolysis or peeling reactions.